The optimal true-ileal-digestible lysine and threonine requirements for growing-finishing pigs from 80 to 130 and 170 to 230 pounds - N Z Frantz; J L Usry; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
A total of 4388 pigs (PIC 337 × C22; Exp. 1: 1070 gilts, initially 79 lb BW; Exp. 2: 3318 pigs, initially 170 lb BW) were used in 28-d growth assays to examine both the true-ileal-digestible (TID) lysine and threonine requirements, and then determine the appropriate TID threonine-to-lysine ratio in growing-finishing pigs from 80 to 130 lb and 170 to 230 lb. In Exp. 1, four TID lysine (0.71. 0.81, 0.91, and 1.01%) and five TID threonine (0.50, 0.56, 0.62, 0.68 and 0.74%) concentrations were evaluated. In Exp. 2, four TID lysine (0.56, 0.64, 0.72, and 0.80%), and five TID threonine (0.43, 0.48, 0.53, 0.58 and 0.63%) concentrations were evaluated. The diet with the highest concentration of lysine and second- highest concentration of threonine served as a positive control in both studies, and this diet was combined as one treatment to give a total of nine treatments in each study. Other amino acids were formulated to meet, or exceed, requirement estimates to ensure that lysine and threonine were the only limiting amino acids. In Exp. 1, increasing TID lysine tended to increase ADG (quadratic, P<0.06), with the greatest response occurring from 0.71 to 0.81%. Increasing TID lysine also quadratically increased ADFI (P<0.03) up to 0.81% TID lysine, and linearly improved feed efficiency (F/G; P<0.01), up to 1.01% TID lysine. Increasing TID threonine did not affect ADG (P>0.69) or ADFI (P>0.29), but improved F/G (linear, P<0.05), with the maximum response occurring at 0.68% TID threonine. Values of 1.01% TID lysine and 0.68% TID threonine in Exp. 1 suggest an optimal TID threonine-to-lysine ratio of 67% for F/G. In Exp. 2, a treatment × gender interaction was observed for F/G (P<0.02). This was because gilts had a greater response to increasing TID lysine, whereas barrows had a greater response to increasing TID threonine. In Exp. 2, increasing TID lysine improved ADG (linear, P<0.05) in gilts and barrows (P<0.07), and improved F/G (linear, P<0.01) in gilts, as the TID lysine concentration increased to 0.72%. Increasing TID threonine improved ADG and F/G (linear, P<0.04) in barrows and increased ADG and ADFI (linear, P<0.06) in gilts as the threonine concentration increased to 0.48%. Values of 0.72% TID lysine and 0.48% TID threonine in Exp. 2 suggest an optimum TID threonine-to-lysine ratio of 67%. The practical TID threonine-to-lysine ratio suggested by this study for pigs from 80 to 130 lb and from 170 to 230 lb is 67%. Further research is needed to verify these results and evaluate the economics of feeding higher threonine concentrations.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Growing pigs; Lysine; Pigs; Threonine; Swine